PRIMA HEALTH: SUATU PENDEKATAN DIGITAL DAN PEMBERDAYAAN KADER UNTUK PENGENDALIAN HIPERTENSI DAN DIABETES BERKELANJUTAN - Muhammad Revi Purnomosidi; MSY. Haura Kaiyyisah Zhafirah; Lucretia Zalfa Shabira; Fannia Yosa Bakhtiar; Daud Aditya Iskandar M.M; Titus Nanda Pratama; Trofi Rizkitama; Ady Akbar (LPPM Universitas Abdurrab, 2026)
This Prima Health Action Research was conducted to develop and implement a comprehensive NCD (Non-Communicable Diseases) management model through preventive, curative, and rehabilitative approaches, based on community participation and digital technology. We integrated training for village health cadres (n = 130) with the utilization of the Prima Health platform as a system for continuous health data recording, monitoring, and analysis. The web-based platform allows systematic documentation of blood pressure, blood glucose levels, and community health activities to support data-driven decision-making at the community level. The five-month action research implementation demonstrated a significant increase in cadres’ capacity to operate health monitoring technology and coordinate routine health checks, with community participation reaching 80%. The use of the digital system contributed to a reduction in uncontrolled hypertension and diabetes cases, as well as improved adherence to physical activity and healthy dietary practices. The intervention effectively lowered blood glucose levels (t = 7.94; p < 0.05) and systolic blood pressure (t = 12.97; p = 0.002) among respondents. These findings indicate that integrating digital technology in Prima Health research effectively strengthens community-based health monitoring systems, enhances intervention responsiveness, and supports the sustainability of NCD management. This model has the potential to be replicated as a technology-based action research approach for strengthening public health systems.